Role of interleukin-4 in human immunoglobulin E formation in hu-PBL-SCID mice. - Spiegelberg, H L (1994)
We studied the role of IL-4 in human IgE formation in severe combined immunodeficient mice engrafted with peripheral blood mononuclear leukocytes (hu-PBL-SCID). PBL from four nonatopic donors produced only small (< 20 ng/ml) or undetectable amounts of IgE in SCID mice whereas engrafted PBL from seven atopic donors secreted IgE with IgE serum levels reaching a mean +/- SE of 184 +/- 37 ng/ml (n = 20). Serum IgE levels peaked 2-3 wk after PBL transfer and declined thereafter with a half-life of 1-2 wk. In contrast, IgG of all subclasses reached maximum serum levels 5-7 wk after PBL transfer and declined little thereafter. Injection of a neutralizing monoclonal antibody to the human IL-4 receptor (IL-4R) on day 0 inhibited completely the IgE formation and caused an approximate twofold reduction of IgG production of all subclasses. The anti-IL-4 R antibody had no effect on IgE secretion when administered 4 wk after PBL engraftment. Incubation of PBL with IL-4 before engraftment resulted in a 10-fold increase in IgE production and could be further enhanced by 100 fold if, in addition to preincubation with IL-4, IL-4 was injected daily for 5 d after PBL transfer. This treatment with IL-4 also induced two- to threefold increase in IgG levels. IFN-gamma had no effect on either IgE or IgG subclass production. In approximately 50% of the mice, one or more IgG subclasses increased disproportionally 5 wk after PBL injection as a result of monoclonal IgG formation. These data demonstrate that PBL from atopic donors secrete IgE in SCID mice in an IL-4-dependent manner, and that IgE production can be enhanced 10- to 100-fold with exogenous human IL-4 in these mice. This mouse model is amenable for the in vivo study of immunomodulators on human IgE formation.